Geographical spread of global emissions: Within-country inequalities are large and increasing - Sauter, Caspar; Grether, Jean-marie; Mathys, Nicole (My University, 2016)
In spite of the extensive literature on greenhouse gas emission inequalities at the world-wide level, most of the evidence so far has been based on country-level data. However, the within-country dimension matters for both the implementation and the policy formation of climate policies. As a preliminary step towards a better understanding of within-country inequalities, this paper measures their extent for the two major greenhouse gases, CO2 and CH4, over the 1970–2008 period. Using Theil-index decompositions, we show that within-country inequalities account for the bulk of global inequality, and tend to increase over the sample period, in contrast with diminishing between-country inequalities. Including differences across sectors reveals that between-sector inequalities matter more than between-country inequalities, and between-sector inequalities become the dominant source of global inequality at the end of the sample period in the CO2 case. Finally, estimated social tensions arising from the disconnection between emissions and future damages turn out to be increasing as soon as within-country disparities are taken into account. These orders of magnitude should be kept in mind while discussing the efficiency and fairness of alternative paths in combating global warming.
Keywords: Global spatial emission inequalities; Sub-national emission inequalities; Theil index decomposition; CO2; CH4; Climate policy